Association of Retinol Binding Protein- 4 (RBP4) with Glycemia, Dyslipidemia, Hypertension, and Obesity in Type 2 Diabetic Iraqi Patients - Jabbar, Thair L.; A. Kasim, Ali (Iraqi Journal of Pharmaceutical Sciences, 2020)
Abstract: Background: Retinol binding protein 4 (RBP4), an adipokine that participate in a lipid metabolism or insulin resistance through a complex regulatory network. Recently, RBP4 was reported to be associated with many cardiovascular diseases (CVDs) risk factors in patients of type 2 diabetes mellitus (T2DM). This study aims to study the correlation of serum RBP4 with some markers of glycemic control, dyslipidemia, hypertension and obesity in T2DM Iraqi patients. Subjects and Methods: one hundred fifty participants were enrolled in this coss-sectional study, 120 of participants were T2DM patients and 30 were apparently healthy individuals to serve as control group. Results: Serum RBP4 levels are higher in T2DM patients with poor glycemic control, dyslipedemia, hypertension, or obesity compared to the control group. Serum RBP4 is positively correlated with body mass index, fasting blood glucose, glycosylated hemoglobin, systolic blood pressure (P<0.001), and plasma triacylglycerols, very low density lipoprotein cholesterol, and low density lipoprotein cholesterol (P<0.05) and negatively correlated with high density lipoprotein cholesterol (P<0.001). Conclusion: serum RBP4 is correlated with many risk factors of CVD in T2DM Iraqi patients. keywords: RBP4, type 2 diabetes mellitus, dyslipidemia, hypertension, obesity